Digitalizacija - izzivi za delovno pravo - Končar, Polonca (Delavci in delodajalci, 2016)
Developments in communication and information technology are leading to new forms of work and to changes in up till nowadays prevailing employment relationships. In addition they are calling into questions issues related to the "subordination", the basic criterion of the employment relationship, to place of work of the digital worker, to working hours and the duration of work, to boundaries between work and private life, to risks of the health at work. The paper draws the attention of the reader to the mentioned issues and the challenges they may represent for the labour law in the time of digitalisation of our societies.
Keywords: delo na domu; delovna razmerja; delovni čas; informacijska tehnologija; komunikacijska tehnologija; teledelo; zaposleni; zdravje pri delu